Uji Konsentrasi Ekstrak Air Daun Lantana camara Linnaeus terhadap Mortalitas dan Perkembangan Spodoptera exigua Hubner (Lepidoptera: Noctuidae): english - Liswarni, yenny; Sari, Nicha Puspita; Hamid, Hasmiandy (Jurnal Proteksi Tanaman (Journal of Plant Protection), 2018)
Spodoptera exigua Hubner is one of the major pests which attack onion crop. Botanical pesticides can be used as an alternative that is cheap, easy and environmentally friendly in controlling these pests. Lantana camara Linn is a plant that has the potential as a botanical pesticide. This study aimed at obtaining the best concentration of water extract of leaves of L. camara which was active on mortality, reduced feeding activity and development of S. exigua in the laboratory. The experiment was conducted using a Completely Randomized Design (CRD), with 6 treatments and 5 replications. The concentration was used a 0%, 2%, 4%, 6%, 8% and 10%. The treatment was done by the application through the larval feed. Parameters observed were larval mortality, reduced feeding activity, duration of larval development, the percentage of pupal, weight of pupal and percentage of adult formed. The results showed that the concentration of water extract of leaves of L. camara as insecticide with LC50 value was 5.02%. Water extract of leaves of L. camara also decreased feeding activity, inhibit development of larval, pupal and adult formed.